ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIK PADA MATERI LINGKARAN SISWA SMP KELAS VIII - Diah Kurniawati; Euis Eti Rohaeti; M Afrilianto (IKIP Siliwangi, 2018)
The Purpose of descriptive qualitative research to describe the problem-solving ability of student mathematics on the material circle for student class VIII SMP in Karawang. The subject of this study consisted of 6 selected students. Data collection techniques using the test. The result of data analysis showed the students beginning ability were included in the low category, because of only about 59% of students from 6 people who are able to solve mathematical problems in the material of the circle.